2000
DOI: 10.1002/1097-0134(20001001)41:1<75::aid-prot100>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Model‐free analysis of a thermophilic Fe7S8 protein compared with a mesophilic Fe4S4 protein

Abstract: 15N T(1), T(2) and (1)H-(15)N NOE were measured for the thermophilic Fe(7)S(8) protein from Bacillus schlegelii and for the Fe(4)S(4) HiPIP protein from Chromatium vinosum, which is a mesophilic protein. The investigation was performed at 276, 300, and 330 K at 11.7 T for the former, whereas only the 298 K data at 14.1 T for the latter were acquired. The data were analyzed with the model-free protocol after correcting the measured parameters for the effect of paramagnetism, because both proteins are paramagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the present study, we have also analyzed the backbone dynamics of both the A. acidocaldarius thioredoxin and its K18G/R82E mutant in a wide temperature range from 25 °C up to 65 °C, so including the growth temperature of the bacterium, which is between 55 and 65 °C (). Even if many studies have been published that report protein backbone dynamics studies as function of temperature ( ), a minor part of them were focused on the mobility of thermostable proteins analyzed in a range comprising the temperature range of growth of their sources.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have also analyzed the backbone dynamics of both the A. acidocaldarius thioredoxin and its K18G/R82E mutant in a wide temperature range from 25 °C up to 65 °C, so including the growth temperature of the bacterium, which is between 55 and 65 °C (). Even if many studies have been published that report protein backbone dynamics studies as function of temperature ( ), a minor part of them were focused on the mobility of thermostable proteins analyzed in a range comprising the temperature range of growth of their sources.…”
Section: Discussionmentioning
confidence: 99%
“…Various experimental methods have been applied to explore protein dynamics adaptation to high temperature. Hydrogen/deuterium (H/D) exchange [22], fluorescence quenching [23], high‐resolution NMR [24] and neutron scattering [25] are probably the major ones. The flexibility of protein molecules is reflected in conformational fluctuations.…”
Section: Experimental Methods Used To Study the Role Of Dynamics In Tmentioning
confidence: 99%
“…We discuss below the results obtained for the axially symmetric case only. By analyzing the τ m values of a group of proteins (6,64,(69)(70)(71)(72), determined experimentally by NMR, versus their molecular volumes (at normalized temperatures), we found that the present τ m values are higher than expected. Since the protein tends to aggregate, care is taken to avoid this possibility.…”
Section: A Comment On the Possible Effects Of Unpaired Electronsmentioning
confidence: 65%
“…Measurement of 15 N relaxation rates has become an important means of studying the backbone dynamics of proteins in solution ( ). They can be conveniently analyzed on the millisecond to microsecond and picosecond to nanosecond time scales ( ).…”
mentioning
confidence: 99%